Second wave COVID crisis, social responsibility and social stigma in India - Madheswaran, Manoj (International Journal Of Community Medicine And Public Health, 2021)
India, the second most populous country in the world and home of 1.30 billion population sees sudden emergence of Coronavirus disease 2019 (COVID-19) since 2020. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is the virus that is responsible for this global pandemic. The origin of this virus is still unknown. This pandemic causes heavy impact on its health infrastructure. Although this pandemic hit at global level, this review is particularly highlight the pandemic situation and how it is being tackled in India. During April and May 2021, due to the high surge of cases, India had reported several million numbers of COVID-19 affected people. During this course of tackling this pandemic, India sees a huge surge of vaccine hesitancy due to various factors. Data suggests that the virus affects younger age groups as well. This review tends to highlight the actual situation and major factors contributed to COVID-19 pandemic in India, also to highlight India’s vaccine policy. To shed light on what went wrong and what can be learned from COVID-19 crisis in India. This data presents important results regarding the COVID‐19 pandemic in India.